The wave - Strasser, Todd. (New York : Dell Laurel-Leaf, 2005)
Presents a fictionalization of a real experiment at a California high school in which a history teacher started a fascist youth movement in an effort to show his students that the Holocaust could indeed happen again.
Booklist.
Young Adult
Keywords: Education -- Experimental methods -- Fiction; Fascism and youth -- Fiction; Education -- Experimental methods -- Fiction; Fascism -- Fiction